(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Rhabdomyolysis was first described as crush syndrome, during the London blitz of world war-ll. lt is a common clinical syndrome resulting from muscle injury there after release of toxic cellular component especially myoglobin. Muscle injury may results from a variety of causes. Most common clinical presentation of rhabdomyolysis is triad of myalgia, weakness and dark colour urine. But presentation may be varied. Very often it causes acute kidney injury and demands renal replacement therapy. Acute Renal Failure (ARF) is usually associated with very high rise of Creatinine Kinase(CK) >10,000 u/L1. In this series, there are few cases with rhabdomyolysis who were admitted and treated in Dhaka Medical College Hospital (DMCH) during July 2010 to April 2011. These cases of rhabdomyolysis normally developed acute kidney injury who were managed with dialysis support. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 93-95